(In)visible harm: Microaggressions and blatant discrimination within the psychological acculturation process of immigrant women in a post-colonial context - Piccinelli, E.; Vauclair, C.-M.; Rudnev, M. (International Journal of Intercultural Relations, 2025)
Objectives. This study examines the unique effects of perceived subtle discrimination (microaggressions) and blatant discrimination on the psychological (mental health, self-esteem), sociocultural (navigating everyday life), and cognitive (social identity) adaptation outcomes of first-generation immigrant women in Portugal. Additionally, we explore the role of different microaggression dimensions, acculturation orientations, and neuroticism in predicting adaptation outcomes. Methods. Data were gathered over two time points, 9–12 months apart, from immigrant women born in the Community of Portuguese Language Countries. Using T1 data (N = 690, Mage = 36.34, SD = 9.11), we ran stepwise regression models to examine the association between microaggressions and blatant discrimination with adaptation outcomes. Then, we computed three cross-lagged panel models (N = 135, Mage = 38.04, SD = 9.07) to establish longitudinal relations among these variables. Lastly, we examined the association between microaggressions dimensions, acculturation orientations, and adaptation outcomes, via three mediation path models using T1 data. Results. Cross-sectional analyses showed that experiences of microaggressions were associated with decreased mental health and self-esteem, increased sociocultural difficulties, and ethnic ingroup identification, over and above the effect of blatant discrimination and neuroticism. Longitudinal results partially supported these findings, indicating that microaggressions (but not blatant discrimination) positively predicted sociocultural difficulties and neuroticism over time. Lastly, microaggressions dimensions showed different associations with adaptation outcomes, while we did not find evidence for the mediating role of acculturation orientations. Conclusions. Although seemingly innocuous, microaggressions are an important factor affecting immigrant women’s adaptation to the receiving society and should be further studied in post-colonial contexts.